Effective kill or trifluralin-susceptible and -resistant green foxtail (Setaria viridis) - Beckie, Hugh J.; MORRISON, IAN N. (1993)
The response of susceptible (S) and resistant (R) green foxtail biotypes to increasing dosages of trifluralin, applied PPI in rapeseed and preemergence incorporated (PEI) in wheat, was investigated in field experiments in 1989 and 1990. Differences in response between fue biotypes to PPI- and PEI-trifluralin were 7- and 12-fold, respectively, based on density and shoot biomass determinations 4 wk after emergence. Nine- and l4-times higher dosages of PPI- and PEI- trifluralin, respectively, were required to reduce R-seed production by 50% than to reduce S-seed production by the same amount. At the recommended trifluralin dosage in rapeseed (1.4 kg ha-!), the density of S-plants 4 wk after emergence was reduced by 84% compared with untreated plots, whereas the density of R-plants was reduced by only 4%. The effective kill (seed yield reduction) was 99% and 42%, respectively. At the recommended dosage in wheat (0.9 kg ha-1), the density of S-plants 4 wk after emergence was reduced by over 99
Sala de Colecciones abiertas
Inglés
x
x
Keywords: Trigo; Triticum aestivum; RESISTENCIA A HERBICIDAS; SETARIA VIRIDIS; HERBICIDAS; Artículos de revista